The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/10615806.2021.1929936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mask-wearing on social anxiety: an exploratory review

Abstract: Background: A unique feature of the global coronavirus pandemic has been the widespread adoption of mask-wearing as a public health measure to minimize the risk of contagion. Little is known about the effects of increased mask-wearing on social interactions, social anxiety, or overall mental health. Objectives: Explore the potential effects of mask-wearing on social anxiety. Design: We review existing literatures to highlight three preselected sets of factors that may be important in shaping the effects of mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 86 publications
5
35
0
Order By: Relevance
“…A study in Italy by Caniato et al ( 35 ) investigated speech intelligibility in classrooms when students and teachers wore face masks, and found that masks overall negatively influence voice propagation especially when it comes to the voice range of male students and regardless of varying indoor acoustic characteristics. Further negative influences of wearing face masks and the correlation with social anxiety and mental health were identified by Saint and Moscovitch ( 36 ) in their exploratory review. A Taiwanese study by Chin et al ( 37 ) shed light on the importance of fear as a driving factor for the public during the COVID-19 pandemic to adhere to protection measures.…”
Section: Literature Reviewmentioning
confidence: 96%
“…A study in Italy by Caniato et al ( 35 ) investigated speech intelligibility in classrooms when students and teachers wore face masks, and found that masks overall negatively influence voice propagation especially when it comes to the voice range of male students and regardless of varying indoor acoustic characteristics. Further negative influences of wearing face masks and the correlation with social anxiety and mental health were identified by Saint and Moscovitch ( 36 ) in their exploratory review. A Taiwanese study by Chin et al ( 37 ) shed light on the importance of fear as a driving factor for the public during the COVID-19 pandemic to adhere to protection measures.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Findings also indicated that lower emotional stability might have the positive effect of encouraging mask uptake among relatively more neurotic individuals, who use masks to protect themselves from threats. However, it is unclear the extent to which mask wearing reduces anxieties (Saint & Moscovitch, 2021 ). Each of these findings speaks to the difficulty of achieving perfect uptake of COVID-19 prevention behaviors when individuals differ in their capacities and motivations to comply (De Carvalho, Pianowski, & Gonçalves, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since individuals with SA are likely to interpret ambiguous cues in negative ways (for a review, see Chen et al ., 2020 ), the ambiguity and uncertainty of social interactions increases, so is the likelihood of negative interpretation. For people with higher levels of SA, masked social encounters may amplify negative interpretation biases by activating their pre-existing vulnerabilities associated with selective memory recall during post event rumination, vigilant-avoidant facial processing, and diminished theory of mind abilities ( Saint & Moscovitch, 2021 ).…”
Section: Impact Of Mask Wearing On Verbal and Nonverbal Communicationmentioning
confidence: 99%